A New England COVID-19 Registry of Patients With CNS Demyelinating Disease: A Pilot Analysis. Issue 5 (September 2021) - Money, Kelli M.; Mahatoo, Ashmanie; Samaan, Soleil; Anand, Pria; Baber, Ursela; Bailey, Mary; Bakshi, Rohit; Bouley, Andrew; Bower, Aaron; Cahill, Jonathan; Houtchens, Maria; Katz, Joshua; et al.
Abstract : Background and Objectives: We sought to define the risk of severe coronavirus disease 2019 (COVID-19) infection requiring hospitalization in patients with CNS demyelinating diseases such as MS and the factors that increase the risk for severe infection to guide decisions regarding patient care during the COVID-19 pandemic. Methods: A pilot cohort of 91 patients with confirmed or suspected COVID-19 infection from the Northeastern United States was analyzed to characterize patient risk factors and factors associated with an increased severity of COVID-19 infection. Univariate analysis of variance was performed using the Mann-Whitney U test or analysis of variance for continuous variables and the χ 2 or Fisher exact test for nominal variables. Univariate and stepwise multivariate logistic regression identified clinical characteristics or symptoms associated with hospitalization. Results: Our cohort demonstrated a 27.5% hospitalization rate and a 4.4% case fatality rate. Performance on Timed 25-Foot Walk before COVID-19 infection, age, number of comorbidities, and presenting symptoms of nausea/vomiting and neurologic symptoms (e.g., paresthesia or weakness) were independent risk factors for hospitalization, whereas headache predicted a milder course without hospitalization. An absolute lymphocyte count was lower in hospitalized patients during COVID-19 infection. Use of disease-modifying therapy did not increase the risk of hospitalization but was associated with an increased need for respiratory support. Discussion: The case fatality and hospitalization rates in our cohort were similar to those found in MS and general population COVID-19 cohorts within the region. Hospitalization was associated with increased disability, age, and comorbidities but not disease-modifying therapy use.